Restorative Justice as An Alternative Paradigm in Conflict Resolution and Justice Restoration - Siria Silubun; Suparno (Al-Makki Publisher, 2026)
Conventional justice, which is primarily oriented toward retribution, often fails to address the root causes of conflict and does not fully meet the needs of all affected parties. This approach tends to position offenders as objects of punishment, without providing adequate opportunities for victims to achieve comprehensive recovery. This study aims to analyze restorative justice as an alternative paradigm that emphasizes the restoration of relationships, recognition of harm, and active participation of all parties in conflict resolution. The research method employed is a qualitative literature review with a comparative analysis approach, examining conventional justice and restorative justice. Data were collected from various scientific literature sources, academic books, research journals, and relevant legal regulations pertaining to the study topic. The results indicate that restorative justice can accommodate victims’ needs, provide offenders with the opportunity to take direct responsibility, and strengthen social relationships within society. This approach emphasizes dialogue, reconciliation, and the restoration of conditions to their pre-conflict state. Its implementation has been relatively effective in contexts such as domestic violence cases, inter-community conflicts, and minor criminal offenses. However, several challenges remain, including limited resources, unequal access, differences in public understanding, and suboptimal integration with the existing criminal justice system. Nevertheless, restorative justice promotes a more humane, participatory, and responsive form of justice. This study concludes that restorative justice is not a full replacement for the conventional justice system but represents a crucial component in building a more balanced, effective, and socially responsive approach to justice.